Deep Rivers: Selected Songs of Florence Price and Margaret Bonds - Peters, Penelope (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 1995)
This essay examines the songs of two African-American women, Florence Price (1888–1953) and Margaret Bonds (1913–72), who embarked upon their compositional studies and careers only a couple of generations after the emancipation. Both discovered in the poetry of Langston Hughes (1902–67) the means for reconciling the musical traditions of their African-American heritage with those of their European training. Through detailed analysis of the textual and musical symbolism in Price's Song to a Dark Virgin and Bonds's The Negro Speaks of Rivers and Three Dream Portraits, the author demonstrates the influence of spirituals ("plantation songs"), blues, and jazz and reveals how these African-American idioms are integrated with the melodic and harmonic idioms from the early twentieth-century European tradition.